Hospitalizations associated with 2009 influenza A (H1N1) and seasonal influenza in Saurashtra region, India - Chudasama, Rajesh K; Patel, Umed V; Verma, Pramod B (The Journal of Infection in Developing Countries, 2010)
Introduction: This study investigated the clinico-epidemiological characteristics of patients who were hospitalized with 2009 pandemic H1N1 influenza virus infection and seasonal influenza in the Saurashtra region of India. Methodology: From September 2009 to February 2010, a total of 773 patients with influenza virus attending different hospitals in Rajkot city were studied. Real-time reverse-transcriptase-polymerase-chain-reaction (RT-PCR) testing was used to confirm infection; the clinico-epidemiological features of the disease were closely monitored. Results: Of the 733 patients, 35.4% (274/773) were cases of 2009 pandemic H1N1 influenza and 64.6% (499/773) were cases of seasonal influenza. Of the 274 patients with 2009 pandemic H1N1 influenza, the median age was 29.5 years, and 51.5% were males. Only 1.1% positive patients had recent travel history to an infected region. A median time of five days was observed from onset of illness to influenza A (H1N1) diagnosis, and a median time of six days was reported for hospital stay. All admitted influenza A (H1N1) patients received Oseltamivir drug, but only 16.1% received it within two days of onset of illness. One fourth of the admitted positive patients died. The most common symptoms were cough, fever, sore throat, and shortness of breath. The coexisting conditions were diabetes mellitus, hypertension, chronic pulmonary diseases, and pregnancy (p = 0.001). Chest radiography revealed 93% of the positive patients had pneumonia. Conclusion: The clinical course and outcomes of the 2009 pandemic (H1N1) influenza virus are comparable to those of the currently circulating seasonal influenza, with high mortality in influenza A (H1N1) patients.